الإستمرار التام لمؤثر أوريسون في فضاء أورليتش (Latakia University Journal -Basic Sciences Series, 2017)
الهدف من هذا البحث هو دراسة وتعميم بعض النتائج المتعلقة بالاستمرار التام لمؤثر أوريسون بمتحولين, والمعطى بمعادلة تكاملية على مجموعة قيوسة وفق قياس لوبيغ, من خلال دراسة التقارب المنتظم لمتتالية من مؤثرات أوريسون , المعطاة بالتوابع , وذلك باستخدام التقارب بالقياس من خلال الإعتماد على شرط كاراثيودوري للمجموعات القيوسة.The aim of this paper is to study and generalize some results that related by the complete continuity of the urysohn.s operator of two variables on a set on which a lebesgue meagure is defined and study uniform convergence sequence of the urysohn .s.operators that defined by functions using convergence meager Depending on caratheodory condition of measurable sets .